Environmental Regulation, Sentiment, and Eco-Innovation: Evidence From China - Sun, Yunpeng; Li, Haoning; Bao, Qun; Lu, Zhou (Frontiers in Environmental Science, 2022)
This study aims to shed light on whether the effects of environmental regulation on China’s eco-innovation driven by the investor sentiment and public sentiment from 2003 to 2017. Adopting a text analysis technique and LSTM model, this study identifies the investor sentiment and public sentiment by the online comments. We find that the environmental regulation has a positive effect on China's eco-innovation through public sentiment, whereas the environmental regulation inhibits the China's eco-innovation through investor sentiment. Second, the regulatory tools of environmental regulation do not only improve the public's enthusiasm and awareness of environmental protection and eco-innovation in China, but also bring the pressure to investors’ survival and continuous innovation. Third, we confirm the environmental regulation has threshold effects on general public sentiment and investor sentiment for affecting China’s eco-innovation. Based on this result, the environmental regulation environmental regulation is easier to trigger public sentiment for affecting China’s eco-innovation. Furthermore,in order to test whether environmental regulation has spatial spillover effect, by constructing the Spatial Durbin model, this study finds that the environmental regulation has spatial spillover effects on Chinese different region’s eco-innovation through two kinds of sentiment. To the policy implication, this study is from two kinds of sentiment to guide the environmental regulators would effectively improve the level of eco-innovation in China.